Potential Obstacles to Achieve Successful Outcomes Following Stuttering Interventions: Potential Obstacles for Stuttering Interventions - Hassan, Alia; Shah, Syed Tariq; Saqulain, Ghulam (Pakistan Journal of Health Sciences, 2025)
Stuttering is a common speech problem affecting all age groups. Speech-language pathologists face barriers in attaining favourable therapeutic results. Identification of these barriers could help attain therapy results. Objectives: To identify the perceived barriers that speech-language pathologists encounter in achieving successful outcomes following stuttering interventions. Methods: The current qualitative study was conducted at Riphah International University from September 2023 to February 2024. A sample of n=10 speech-language pathologists was taken from Rawalpindi and Islamabad using purposive sampling. The sample included qualified speech-language pathologists of both genders, any age, practicing for at least 05 years with clients having fluency disorder. The study involved semi-structured interviews with the option of face-to-face and online interviews using an interview guide. Information obtained was transcribed followed by thematic analysis. Results: The study revealed six major themes including collaborative approaches in intervention and the role of various professionals, Patient engagement and empowerment for successful intervention outcomes, empowering families for effective communication and support in successful intervention, strengthening speech-language pathologists' practices, therapeutic accessibility and holistic approach to stuttering intervention. The findings demonstrated that speech-language pathologists understanding of stuttering especially their unique roles within it, is somewhat restricted due to barriers including i). Diverse perspective held by the speech-language pathologists, ii) Clinical challenges, iii) Systematic and environmental factors and iv) lack of collaboration and support. Conclusions: It was concluded that speech-language pathologists perceive the following main barriers i) Diverse perspectives held by the speech-language pathologists, Clinical challenges, Systematic and environmental factors and lack of collaboration and support.